Experiences of digital exclusion and the impact on health in people living with severe mental illness - Middle, Rachael; Welch, Lindsay (Frontiers in Digital Health, 2022)
Background: The covid-19 pandemic has accelerated the use of digital tools within health and social care services. However, for a range of different reasons, across the UK there continue to be people who are digitally excluded. People living with a disability have been identified as being more likely to be digitally excluded and many of these people, including people with severe mental illness (SMI) already experience health inequalities. Therefore, understanding the perceived impact digital exclusion has on health and potential facilitators of increased inclusion is an important area for research. This study had two aims: 1. To understand experiences of digital exclusion and health in people with SMI 2. To explore the influences and mechanisms which would increase engagement with digital health tools Methods: This was an observational qualitative study, conducting focus groups (with the option of a 1:1 interview for those uncomfortable in groups) with nine people with severe mental illness. Results: Participant’s responses were themed in to four key areas in relation to digital exclusion and impact on health: 1. Reduced social connectedness, 2. The impact on wider determinants of health 3. Negative perception of self, 4. Disempowerment. Key facilitators for increased engagement with digital tools included, local digital skills support with mental health lived experience involvement in the delivery, digitally engaged social referents, access to digital tools and data, personalised and straightforward digital tools. In addition, increasing health and social care staff’s awareness of digital exclusion was also viewed as important in promoting inclusion. Conclusion: The research findings suggest that digital inclusion should be viewed as a wider determinant of health. Many of the identified consequences of exclusion are particularly important in relation to mental health and mental health recovery. This research suggests that identifying and addressing digital exclusion should be viewed as a priority for mental health services.